The impact of photoactivation on the antibacterial effect of nanoparticles obtained by pulsed laser ablation - Goncharova, Darya A.; Nemoykina, Anna L.; Trufanov, V. O.; Kulinich, Sergei A.; Svetlichnyi, Valerii A. (Proceedings of SPIE)
This paper studies the influence of photoactivation on the antibacterial activity of nanoparticles (NPs) obtained by pulsed laser ablation (PLA) of a brass target. The initial composition of the target is presented by a cubic phase is Cu65Zn35/Cu50Zn50. PLA in water was found to produce Cu2O and ZnO NPs. Generation of a different phase of brass (Cu85Zn15) was also observed. A number of studies was conducted to test the antibacterial properties of cotton treated with colloidal solution. Strain of S.aureus bacteria was used to evaluate antibacterial activity of prepared NPs, and it turned out to be high enough; an additional exposure of red light (610 nm) did not induce any changes in the antibacterial activity of the samples. Irradiation of the -soft‖ ultraviolet (365 nm) led to a sharp spike of the antibacterial activity and complete death of bacteria.